VD_FINDINFO Décision / 2017 / 295 vom 7. April 2017 - VD Tribunal cantonal (2017)
DROIT D'ÊTRE ENTENDU, ANONYMAT, CONSULTATION DU DOSSIER, PREUVE ILLICITE, REPRÉSAILLES, DÉNONCIATEUR, POLICE, IDENTITÉ | 102 CPP (CH), 107 CPP (CH), 108 CPP (CH), 139 CPP (CH), 149 CPP (CH)